The mungbean VrP locus encoding MYB90, an R2R3-type MYB protein, regulates anthocyanin biosynthesis - Lin, Yun; Laosatit, Kularb; Liu, Jinyang; Chen, Jingbing; Yuan, Xingxing; Somta, Prakit; Chen, Xin (Frontiers in Plant Science, 2022)
Anthocyanins are water-soluble pigments present in several tissues/parts of plants. The pigments provide color and are wildly known for health benefits for human, insect attraction for plant pollination and stress resistance in plants. Anthocyanins content variations in mungbean (Vigna radiata (L.) Wilczek) were first noticed a long time ago, but the genetic mechanism controlling the anthocyanins in mungbean remains unknown. Two F2 populations derived from the crossed between purple-hypocotyl (V2709 and Guilv1) and green-hypocotyl (Sulv1 and Kamphaeng Saen 2 (KPS2)) mungbeans were used to map the VrP locus controlling purple hypocotyl. The VrP locus was mapped to a 78.9-kb region on chromosome 4. Sequence comparison and gene expression analysis identified an R2R3-MYB gene VrMYB90 as the candidate gene for the VrP locus. Haplotype analysis using 124 mungbean accessions suggested that 10 SNPs in exon 3 may lead to an abolished expression of VrMYB90 and an absence of anthocyanins accumulation in hypocotyl of Sulv1 and KPS2. The overexpression of VrMYB90 in mungbean hairy root, tobacco leaf and Arabidopsis resulted in anthocyanin accumulation (purple color). Gene expression analysis demonstrated that VrMYB90 regulated anthocyanins accumulation in hypocotyl, stem, petiole and flowers, and the expression was sensitive to light. VrMYB90 protein may upregulate VrDFR encoding dihydroflavonol 4‐reductase at the late biosynthesis step of anthocyanins in mungbeans. These results suggested that VrMYB90 is the dominator in the spatiotemporal regulation of anthocyanin biosynthesis. Our results provide insight into the biosynthesis mechanism of anthocyanin and a theoretical basis for breeding mungbeans.